Smart Farming: Improving Agricultural Productivity and Efficiency using Robotics Technology - Anaam, Wahyu Syaiful; Saputra, Wahid Ivan; Rohman, Andhi; Anggraeni, Martha Richa; Rafli, Muhammad; Ghufron, Ghufron (INDONESIAN JOURNAL OF SUSTAINABILITY, 2024)
Agriculture is a vital sector in providing food for the world's growing population. However, challenges such as climate change, limited land, and a lack of skilled agricultural labor have driven the development of innovative agricultural technologies. One promising solution is the use of robots in agriculture. This paper discusses robotic farming, namely the use of robots and related technology in agricultural activities. The main focus is to explain the benefits, applications, and challenges associated with the use of robotic technology in agriculture. In this paper, several examples of the implementation of robotic technology in agriculture will also be discussed.